2020
DOI: 10.1515/gps-2020-0065
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of six different methods in green synthesis of selenium nanoparticles using propolis extract: Screening and characterization

Abstract: Selenium nanoparticles (Se NPs) were fabricated with propolis hydro-alcoholic extract and six different methods, namely, hydrothermal, microwave irradiation, ultrasonication, UV radiation, self-assembling, and conventional heating. Results indicated that antioxidant activity, turbidity, pH, and brix values of the provided hydroalcoholic propolis extract were 85.8%, 2.235% a.u., 4.1, and 3.2°Bx, respectively. Gas chromatography analysis revealed that approximately 38 bioactive compounds were detected in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The comparison between six different methods of preparing nanopropolis was made in a study in which the hydroalcoholic extract of propolis was used to prepare selenium NPs (SeNPs) by hydrothermal, microwave irradiation, ultrasonication, UV-radiation, self-assembling, and conventional heating methods (Hatami, Javadi, & Jafarizadeh-Malmiri, 2020). In this study, 200 μl of the prepared propolis extract was added to 20 ml of 10 mM of selenium salt solution and the NPs were prepared using six different methods.…”
Section: Methods For the Preparation Of Nanopropolismentioning
confidence: 99%
“…The comparison between six different methods of preparing nanopropolis was made in a study in which the hydroalcoholic extract of propolis was used to prepare selenium NPs (SeNPs) by hydrothermal, microwave irradiation, ultrasonication, UV-radiation, self-assembling, and conventional heating methods (Hatami, Javadi, & Jafarizadeh-Malmiri, 2020). In this study, 200 μl of the prepared propolis extract was added to 20 ml of 10 mM of selenium salt solution and the NPs were prepared using six different methods.…”
Section: Methods For the Preparation Of Nanopropolismentioning
confidence: 99%
“…However, negative surface charge prevents situations that cause instability such as fluctuation and clustering. [78][79][80] A study conducted in the literature found that the surface charge of SeNPs was 24.7 mV. [81] 3.1.6 | UV-Vis spectroscopy data CF plant and sodium selenite solution were mixed in a ratio 2:3, and observations were made from that moment on.…”
Section: Dls Zetasizermentioning
confidence: 99%
“…Various reports showed that propolis is composed of different bioactive compounds (such as flavanones, flavones, alcohols, aldehydes, esters, aromatic acids, etc.) that can synthesize NPS by metal ion reduction to their elements (Kumar et al 2014 ; Hatami et al 2020 ). Shubharani et al ( 2019 ) investigated the synthesis of Se NPs by hydroalcoholic extract of bee propolis (with size ranged of 52.9–118 nm).…”
Section: Synthesis Of Se Npsmentioning
confidence: 99%
“…They revealed the antioxidant, antibacterial, and antifungal activity of Se NPs biosynthesized with ethanol extract of bee propolis (Shubharani et al 2019 ). Se NPs biosynthesized by bee propolis hydroalcoholic extract with the size range of 50–60 nm and six different heating methods, namely, microwave, conventional heating (mild heating by heater and stirrer), ultrasonication, self-assembling, hydrothermal, and UV irradiation (Hatami et al 2020 ). Hatami et al ( 2020 ) demonstrated that bee propolis extract, due to the presence of natural reducing and stabilizing agents, had potential application in the biosynthesis of Se NPs.…”
Section: Synthesis Of Se Npsmentioning
confidence: 99%
See 1 more Smart Citation